التصنیف العنکبوتى للأرشیفات : دراسة تقییمیة للأرشیفات الوطنیة العربیة على الانترنت فى ضوء اسلوب القیاسات العنکبوتیة - د. عبد الرحمن فراج (المجلة الدولية لعلوم المكتبات والمعلومات)
Recently, the international and national agencies have paid attention oninstitution ranking, top of which are universities and academic institutes. Theinstitution ranking helps unveil the institute ranking and quality. This is why it is asignificant indicator on assessing the institution position and stature amongstother domestic and international institutions. It functions a reliable reference onmotivating institutes to have visibility. The study targets probing how far the Arabnational archives benefit from the information and communication technologies insupporting functions and services, particularly, their websites deemed one of theimportant Arabic content resources. Further, on reliance to Webometrics, thestudy targets unveiling the quality and impact of the Arab national archivesWebsites and the ranking of each Website. It mirrors the Arab archivessignificance on the electronic environment. The study concludes somerecommendations targeting sending the Arab national archives ranks higher andsupporting their functions and services on the Internet.